Participation without Negotiating: Influence of Stakeholder Power Imbalances and Engagement Models on Agricultural Policy Development in Uganda. (14th August 2018) - Yami, Mastewal; van Asten, Piet; Hauser, Michael; Schut, Marc; Pali, Pamela
Abstract: Although the political context in Uganda exhibits democratic deficit and patronage, research and development actors have given little attention to the possible negative impact these may have on agricultural policymaking and implementation processes. This article examines the influence of power in perpetuating prevailing narratives around public participation in agricultural policymaking processes. The analysis is based on qualitative data collected between September 2014 and May 2015 using 86 in‐depth interviews, 18 focus group discussions, and recorded observations in stakeholder consultations. Results indicate that while the political setting provides space for uncensored debates, the policymaking process remains under close control of political leaders, technical personnel, and high‐level officers in the government. Policy negotiation remains limited to actors who are knowledgeable about the technical issues and those who have the financial resources and political power to influence decisions, such as international donors. There is limited space for negotiation of competing claims and interests in the processes by public and private actors actively engaged in agricultural development, production, processing, and trade. Thus, efforts to achieve good governance in policy processes fall short due to lack of approaches that promote co‐design and co‐ownership of the policies.